Nursing students’ perceptions of spiritual needs at the end of life. A qualitative study - García-Navarro, E. Begoña; Navarro, Sonia García; Sousa, Luis; José, Helena; Caceres-Titos, María José; Ortega-Galán, Ángela (Frontiers in Psychiatry, 2023)
Spirituality is defined as the meaning of life, being the very essence of life made up of all of the aspects inherent to it. During end-of-life processes, this need is shown to be particularly altered in patients and yet it is an aspect that the health professionals accompanying patients in this situation report being least equipped to address, alongside therapies that could help to meet these needs, such as art therapy. An exploratory qualitative study was conducted with a phenomenological approach. Content analysis was conducted, according to that described by Taylor and Bodgan, of semi-structured interviews. The present research adheres to the guidelines of COREQ and was conducted with final year students undertaking a Nursing degree at the University of Huelva, Spain. The sample was selected via intentional sampling using snowball recruitment from the study population. Stratification according to gender was performed due to the feminised nature of the population. Sample size was determined progressively during the course of the research, with recruitment ceasing at 13 informants once information saturation was achieved. Inclusion criteria required that participants were to be final year students enrolled on a Nursing degree who had provided consent to participate voluntarily in the research. The present study identified the lack of training received by nursing professional on spirituality, although they proved to have the necessary skills and tools to address this issue, with such skills being acquired in training received throughout the academic year. Students stated that they needed to be equipped with strategies to help them become familiar with this reality for end-of-life accompaniment, via art therapy, as creativity was the ability that most helped them get in touch with the meaning of life.